Cytologic and Histologic Aspects of High-Grade Transformation of Salivary Gland Carcinoma. Issue 5 (September 2020) - Nakaguro, Masato; Faquin, William C.; Sadow, Peter M.
Abstract : Abstract: High-grade transformation (HGT) is a process whereby low- to intermediate-grade carcinomas transform into high-grade, poorly differentiated, or undifferentiated carcinomas. In salivary gland tumor pathology, several terminologies, including dedifferentiation or hybrid tumor, have been adopted to describe tumors that do not fit into one distinct tumor type. As HGT confers a poor prognosis despite initial tumor type, the finding of HGT must be recognized for optimal patient management. Preoperative fine-needle aspiration biopsy is typically positive for malignancy, but the recognition of both low- and high-grade components is not always possible and, if only the latter present, may obscure the tumor subtype from which the HGT derives. Most HGTs occur in association with acinic cell carcinoma and adenoid cystic carcinoma, but have also been seen with epithelial-myoepithelial carcinoma, secretory carcinoma, and mucoepidermoid carcinoma.